Navigating Second Generation Memory and Auto/ biography in Home Video. A Video Collection of Hojda Stojka, Son of Artist and Survivor of the Porajmos Ceija Stojka (Studia austriaca, 2023)
This paper investigates home videos made by Hojda Stojka, the son of Ceija Stojka (1933-2013), artist and survivor of Auschwitz, Ravensbrück, and Bergen-Belsen. Based on a close reading of significant video sequences, a narrative interview with the videographer, and Ceija Stojka’s publications and films, it analyses how the auto/biographical videos relate to the persecution of the parents’ generation. The paper focuses on the importance of spaces like kitchens, cars and stages, on the value assigned to auto/biographical audiovisual recordings, and the recontextualization and integration of photographs and television recordings into the family memory.